Tinjauan Maqashid al-Syari’ah Terhadap Akad-akad Pernikahan Kontemporer - Hidayanti, Sri (Jurnal Indragiri Penelitian Multidisiplin, 2024)
Maqashid Al-Syariah and marriage have a close relationship and cannot be separated. Because the most important goal of marriage is to worship toward Allah SWT. In this modern era, there are many marriage contracts that have developed throughout the world, which are not in accordance with Maqashid Al-Syariah, such as Mut’ah’s marriage, Sirry’s marriage, Misyar’s marriage, Asdiqa’s marriage and so on. Its influence is very dangerous for husbands, wives, children and society. As for the packaging is only a little compared to the worse. Therefore, Maqashid Al-Syariah prohibited it. The purpose of the Maqashid Al-Syariah is reduced to safeguard religion, soul, descent, wealth and reason.